Seasonal variance of 25-(OH) vitamin D in the general population of Estonia, a Northern European country - Kallikorm Riina; Kull Mart; Tamm Anu; Lember Margus (BMC, 2009)
Abstract Background Vitamin D has a wide variety of physiological functions in the human body. There is increasing evidence that low serum levels of this vitamin have an important role in the pathogenesis of different skeletal and extra-skeletal diseases. Vitamin D deficiency and insufficiency is common at northern latitudes. There are few population-based studies in the northern European region looking at the issue in a wider age group. We aimed to measure Vitamin D level in the general population of Estonia (latitude 59°N), a North-European country where dairy products are not fortified with vitamin D. Methods The study subjects were a population-based random selection of 367 individuals (200 women and 167 men, mean age 48.9 ± 12.2 years, range 25-70 years) from the registers of general health care providers. 25-(OH) vitamin D (25(OH)D) level and parathyroid hormone (PTH) were measured in summer and in winter. Additionally age, sex, body mass index (BMI) and self-reported sunbathing habits were recorded. Results The mean serum 25(OH)D concentration in winter was 43.7 ± 15 nmol/L and in summer 59.3 ± 18 nmol/L (p < 0.0001). In winter 73% of the subjects had 25(OH)D insufficiency (25(OH)D concentration below 50 nmol/L) and 8% had deficiency (25(OH)D below 25 nmol/L). The corresponding percentages in summer were 29% for insufficiency and less than 1% for deficiency. PTH reached a plateau at around 80 nmol/L. BMI and age were inversely associated with 25(OH)D, but lost significance when adjusted for sunbathing habits. A difference in the seasonal 25(OH)D amplitude between genders (p = 0.01) was revealed. Conclusion Vitamin D insufficiency is highly prevalent throughout the year in a population without vitamin D dairy fortification living at the latitude of 59°N.